Pupil Size as a Window on Neural Substrates of Cognition - Joshi, Siddhartha; Gold, Joshua I. (Trends in cognitive sciences, 2020)
Cognitively driven pupil modulations reflect certain underlying brain functions. What do these reflections tell us? Here, we review findings that have identified key roles for three neural systems: cortical modulation of the pretectal olivary nucleus (PON), which controls the pupillary light reflex; the superior colliculus (SC), which mediates orienting responses, including pupil changes to salient stimuli; and the locus coeruleus (LC)-norepinephrine (NE) neuromodulatory system, which mediates relationships between pupil-linked arousal and cognition. We discuss how these findings can inform the interpretation of pupil measurements in terms of activation of these neural systems. We also highlight caveats, open questions, and key directions for future experiments for improving these interpretations in terms of the underlying neural dynamics throughout the brain. Recent years have seen a surge in interest in using pupil size to gain insights into how the brain processes information in the context of a broad range of behavioral tasks; for example, a search for ‘pupil’ and ‘behavior’ returned a list of around three studies/year from 1967 to 2008 and >15 studies/year from 2009 to 2019.A growing body of anatomical and functional work has identified key roles for three brain regions in funneling cognitively relevant information to brainstem circuits that control the pupil: the PON, intermediate layers of the SC (SCi), and LC.Based on these findings, measures of baseline and evoked changes in pupil diameter can be interpreted in terms of activation of these regions and, in some cases, the cortical and subcortical sources of the cognitive signals that drive them.Emerging techniques are beginning to allow us to: (i) assess relationships between pupil size and neural activity measured simultaneously in multiple brain regions; (ii) test for causal roles of circuits involving the PON, SCi, and LC in controlling pupil; and (iii) determine the context dependence of these roles by using carefully controlled behavioral tasks.